PENGARUH PENILAIAN TINGKAT KESEHATAN TERHADAP KECUKUPAN MODAL PADA BANK SYARIAH DI INDONESIA (PERIODE 2010-2014) - B31112102, Fitriyani (Jurnal Manajemen Update, 2016)
Capital Adequacy Ratio (CAR) is an important indicator of capital adeguacy in the bank health assessment. The bank capltal indicator should be prioritized given in its mechanism banking is an industry that relies on public trust. A healthy bank which can be seen from its capital indicators should be the basis for the community to establish trust in the bank. In this research, there are three variables that affect capital adequacy. The three variables are; Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Expenses Operating Income (OEOI). The aim of this study is to find out the effect of Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Expenses Operating Income (OEOI) on the capital adequacy of Sharia banks in Indonesia. The samples in this study were 11 Sharia banks in Indonesia. The selection of the samples used a nonprobability sampling (a sampling total) technique. The multiple regression test was used to analyze the data which is preceded by the classical assumption test consisting of normality test and heteroscedasticity test. The hypotheses were tested using the F test and t test with significance level o = 0.05. The findings indicate that the NPF had significant negative effect on capital adequacy; FDR had an insignificant positive effect on capital adequacy; and OEOI had an insignificant negative effect on capial adequacy. Keywords: Non Performing Fiturrcing(NPF), Financing to Deposit Ratio(FDR), Operating Expenses to Operating Income(OEOI) and Capital Adequacy Ratio (CAR)